Upaya Identifikasi dan Mengembangkan Minat Bakat Peserta Didik Saat Pandemi di SD Islam Al Fattaah - Magdalena, Ina; Sipayung, Kristin Novita Sari; Sari, Putri Indah; Milawati, Siti Santi (ANWARUL, 2022)
Every child has different abilities and cognitive abilities. This is motivated by heredity and environmental factors. Hereditary factors can be from the father's or mother's genes. One example of environmental factors is how to educate parents about their children or the good and bad of the surrounding environment. That is why parenting and the environment have a big influence on the quality of children. Most elementary school children have not been able to recognize their identity and have not been able to develop the abilities that exist in themselves. The purpose of this study is to describe the method of identifying and developing interests and talents for the students of Al-Fattaah Islamic Elementary School. This study uses a qualitative method with a descriptive qualitative design (case study). The data collection technique used direct interviews with the deputy head of the Al Fattaah Islamic Elementary School curriculum. Developing talent with some effort is quite effective to do. This can be seen from the results of interviews received by interviewers that with the existence of extracurricular and four aspects, namely academic, skills, character, and spiritual in learning activities, students can find interests and talents. Where these interests and talents will be developed by the Al Fattaah Islamic Elementary School teachers.